The Flavonoid Cyanidin Shows Immunomodulatory and Broad-Spectrum Antiviral Properties, Including SARS-CoV-2 - Vicente, Josefina (2023)
New antiviral treatments are needed to deal with the unpredictable emergence of viruses. Furthermore, vaccines and antivirals are only available for just a few viral infections, and antiviral drug resistance is an increasing concern. Cyanidin (a natural product also called A18), a key flavonoid that is present in red berries and other fruits, attenuates the development of several diseases, through its anti-inflammatory effects. Regarding its mechanism of action, A18 was identified as an IL-17A inhibitor, resulting in the attenuation of IL-17A signaling and associated diseases in mice. Importantly, A18 also inhibits the NF-κB signaling pathway in different cell types and conditions in vitro and in vivo. In this study, we report that A18 restricts RSV, HSV-1, canine coronavirus, and SARS-CoV-2 multiplication, indicating a broad-spectrum antiviral activity. We also found that A18 can control cytokine and NF-κB induction in RSV-infected cells independently of its antiviral activity. Furthermore, in mice infected with RSV, A18 not only significantly reduces viral titers in the lungs, but also diminishes lung injury. Thus, these results provide evidence that A18 could be used as a broad-spectrum antiviral and may contribute to the development of novel therapeutic targets to control these viral infections and pathogenesis.